PENGARUH PERENCANAAN PAJAK, PAJAK TANGGUHAN, DAN PAJAK KINI TERHADAP MANAJEMEN LABA DENGAN LAVERAGE SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR SUB SECTOR MAKANAN & MINUMAN YANG TERDAFTAR PADA BEI TAHUN 2018-2020 - Enggar Nursasi; Siti Maghfiroh; Triana Murtiningtyas (Jurnal Manajemen Dirgantara, 2023)
The purpose of this study is to analyze tax planning, deferred tax and current tax on earnings management with leverage as a moderating variable. The object of this research is the food & beverage sub-sector manufacturing companies listed on the IDX for 2018-2020, the population in this study is 51 companies, and a sample of 22 companies obtained from the purposive sampling method. The method of data analysis in this study is the inner model using the R-Square value and hypothesis testing using the T-statistic value and p-values. Data processing in this using smarpls 3.29 software. The results showed that tax planning, deferred taxes, and current taxes have an effect on earnings management. Leverage is able to moderate tax planning, deferred tax on earnings management, and leverage is not able to moderate current tax on Profit Management.